Delusion-like experiences are related to negative perceptions of self and others in non-clinical individuals. Issue 3 (3rd July 2022) - Zamperoni, Georgia; Neill, Erica; Rossell, Susan L.; Tan, Eric J.
ABSTRACT: Background: Delusions are a core feature of psychosis and are thought to exist on a continuum from healthy individuals to clinical populations. This study examined the relationship between delusion-like experiences, using the Peters Delusional Inventory (PDI), and two aspects of personal worldview: core schemas (positive and negative views of the self and others) and locus of control (LOC). Methods: 258 healthy participants without a history of psychiatric illness completed an online survey assessing these constructs. Stepwise regression controlling for age and negative affect, revealed that negative self-schemas significantly predicted the presence of delusion–like experiences whilst negative schemas of others significantly predicted both the presence of delusion–like experiences and associated levels of distress and preoccupation. Results: Positive schemas did not relate to delusions as measured by the PDI. Hierarchical regression demonstrated that LOC did not significantly predict delusion–like experiences. Discussion: The findings highlight that negative schemas of others may be more critically related to delusional experiences than negative self-schemas. Replication in clinical samples is required, while some implications for future research and clinical interventions in prodromal psychosis are examined.